Pain Control In Cancer Patients By Opiate Use - Mohagheghi M A (Tehran University Medical Journal, 2003)
Opioids are increasingly being recognized as the primary treatment for cancer pain management. Optimal treatment of cancer pain involves assessing its characteristics, considering different management strategies, evaluating side effects and adverse drug reactions and establishing the most appropriate therapeutic regimen. This study was designed to review the current status of pain management for advanced cancer cases using opioid analgesics."nMaterials and Methods: A questionnaire was used to collect data on demographics, disease characteristics, and opioids use indicators in 700 cases of advanced cancer patients."nResults: A total of 700 cancer cases, 42 percent females and 58 percent males, between 17-80 years age range (Mean age of 57.25) were studied retrospectively. Cancers of breast (21 percent), colorectal (12 percent), lung (7 percent), stomach (7 percent) and bone either primary or metastatic (6 percent ) in women and stomach (17 percent), lung (12 percent), colorectal (11 percent), prostate (9 percent ), and bone (8 percent ) in men were the most common causes of opioids prescription in study group respectively. Advanced primary cancer (in 52 percent), bone metastasis (in 32 percent), and treatment complications (in 7 percent ) were considered as physical basis for pain in patients. Morphine (by injection), Opium (by oral intake) and methadone (injection and/or oral) were the most common opioids prescribed. Using equianalgesic conversion chart, the daily dosages and therapeutics schedules of morphine administration were as follows:"n43 percent received 21-30 mg. in 2-4 divided doses"n27 percent received >30 mg. in 3-5 divided doses"n21 percent received 11-20 mg. in 2-3 divided doses"n9 percent received 5-10 mg. in 1-2 divided doses"nConclusion: Pain management of cancer patients is not adequate and opioid use is not rational. New educational and managerial strategies are needed to optimize cancer pain treatment in routine medical practice. To overcome current barriers, WHO stepwise model for cancer pain control and palliative care is recommended. Publishing Standard Treatment Guidelines for different levels of health care system is another recommended approach to optimize cancer pain."n